Strategi Pemanfaatan Lahan Mangrove untuk Pengelolaan Tambak Berkelanjutan di Kabupaten Lombok Timur Bagian Selatan, Nusa Tenggara Barat - Johari, Harry Irawan (Jurnal Ilmu Kelautan Kepulauan, 2025)
Mangrove ecosystems play a critical role in supporting sustainable aquaculture through the provision of ecological services, social benefits, and economic contributions. However, increasing pressures from land conversion and unsustainable aquaculture practices have triggered significant ecosystem degradation in the coastal region of South East Lombok Regency. This study aims to formulate strategies for mangrove land utilization that promote sustainable aquaculture management by integrating ecological, social, and economic considerations. The research employed a descriptive-analytical approach combining biophysical assessment, economic valuation, and socio-cultural analysis of coastal communities. Primary data were collected through field observations and interviews, while secondary data were derived from satellite imagery interpretation and scientific publications. Strategic formulation was conducted using the integration of SWOT analysis and the Analytical Hierarchy Process (AHP) to generate measurable and prioritized management options. Findings reveal that mangrove ecosystems in Ekas Bay, Sunut Bay, and Jor Bay still retain substantial ecological potential despite varying levels of degradation. The estimated total economic value of mangroves reaches approximately IDR 104 million/ha/year, dominated by direct benefits from fisheries and indirect benefits from coastal protection. Financial analysis indicates that aquaculture operations appear feasible when environmental costs are excluded, whereas economic analysis incorporating ecological costs deems them unviable. Through the integration of SWOT–AHP, key strategies recommended include the promotion of silvofishery models, rehabilitation of degraded mangrove areas, and enhanced community participation in coastal resource management. Overall, this study underscores the necessity of an integrative governance framework in which ecological sustainability serves as the foundation for aligning social and economic dimensions. The proposed strategies are expected to provide a reference for policy-making toward sustainable aquaculture development in coastal regions